Hector SLAM 2D Mapping For Simultaneous Localization And Mapping (SLAM) - Saat, Shahrizal; Mohd Fozi, Airini An Nadrah; Saealal, Muhammad Salihin; Abd Rashid, Wan Norhisyam; Mohd Sani, Farees Ezwan (Medwell Journals, 2019)
This study presents an application of LiDAR sensor for 2D mapping construction in an unknown environments and capability to localize its own location based on landmark detected. Previously, there are various research actively conducted by others researchers for SLAM application. In general, it can be categorized based on three different type of sensor measurement and technique such as vision based SLAM, RGB-D based SLAM and also laser based SLAM. The main focus in this project is to present an experiment result conducted of a Simultaneous Localization and Mapping (SLAM) application based on laser sensor which is LiDAR in term of capability of mapping construction and localization it self. LiDAR sensor is put on the vehicle that will operate in real-world environments and computational processing done by using Robotic Operating System (ROS). This project is tested and verified in a curtain room with several parameter by using Robot Operating System (ROS). SLAM was implemented to provide localization estimates in environments where there are static landmarks that are only rarely recognized by the vehicle or robot. This project also, consider the features that enter and leave the environment as temporary landmarks that can be used in combination with the rarely seen static landmarks. As conclusion, performance of SLAM by using LiDAR sensor can be apply for several robotic system such as flight control, obstacle avoidance, navigation and other function in the future application.